Chinese aid and health at the country and local level - Cruzatti, John; Dreher, Axel; Matzat, Johannes (CESifo working papers, 2020)
We investigate whether and to what extent Chinese development finance affects infant mortality, combining 92 demographic and health surveys (DHS) for a maximum of 53 countries and almost 55,000 sub-national locations over the 2002-2014 period. We address causality by instrumenting aid with a set of interacted variables. Variation over time results from indicators that measure the availability of funding in a given year. Cross-sectional variation results from a sub-national region's "probability to receive aid." Controlled for this probability in tandem with fixed effects for country-years and provinces, the interactions of these variables form powerful and excludable instruments. Our results show that Chinese aid increases infant mortality at sub-national scales, but decreases mortality at the country-level. In several tests, we show that this stark contrast likely results from aid being fungible within recipient countries.